Architecture of NaFe(MoO4)2 as a novel anode material for rechargeable lithium and sodium ion batteries - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Praveen, C. S.; Dwivedi, Pravin Kumari; Karbhal, Indrapal; Gosavi, Suresh W.; Shelke, V, Manjusha; Kale, Bharat B. (Applied Surface Science, 2021)
In recent decades, particular focus has been given to enhance the capacity of LIBs and SIBs either by developing new materials or by modifying existing materials. Hence, we have demonstrated a new anode material i.e. sodium iron molybdate [NaFe(MoO4)2] for both LIBs and SIBs. NaFe(MoO4)2 has been successfully synthesized by solid-state combustion technique and tested as a promising new anode material for both LIBs and SIBs. A detailed analysis of the crystal structure has been performed using DFT calculations. NaFe(MoO4)2 crystallizes in the monoclinic phase with the space group C2/c (#15). FESEM also shows highly crystalline monoclinic shaped crystals of micron size. When evaluated as an anode material for LIBs, NaFe(MoO4)2 electrode exhibited electrochemical capacity of 920 mAhg- 1 in the second cycle at the current density of 50 mAg-1. Though capacity decreases on further cycling, the coulombic efficiency was maintained at 99% for 50 cycles. Significantly, a high discharge capacity of 100 mAhg- 1 was maintained at a very high rate of 1 Ag-1. On the other hand, we have also tested NaFe(MoO4)2 for SIBs which shows excellent reversible specific capacity i.e. 100 mAhg- 1 at the current density of 100 mAg-1 even after 500 cycles. This novel system has shown good stability for LIBs and SIBs which is hitherto unattempted.
Keywords: Electrochemical study; lithium-ion battery; Morphology; NaFe(MoO4)2; Sodium-ion battery